Three-dimensional assessment of condyle and glenoid fossa changes after treatment with the twin block and herbst appliances - Velentza , Marıa-Foteini (My University, 2014)
TWİN BLOK VE HERBST APAREYİ İLE TEDAVİ SONRASI KONDİL VE GLENOİD FOSSADA MEYDANA GELEN DEĞİŞİKLİKLERİN ÜÇ BOYUTLU OLARAK DEĞERLENDİRİLMESİ MARIA-FOTEINI VELENTZA

Bu araştırmanın amacı, Twin Block veya Herbst apareyi ile tedavi görmüş olan iskeletsel Sınıf II hastaların, kondil ve glenoid fossa bölgelerinde meydana gelmiş olan 3 boyutlu değişikliklerin değerlendirilmesi ve karşılaştırılmasıdır. 29 tane Sınıf II Divizyon I iskeletsel ilişkiye sahip, fonksiyonel çene ortopedisi ile tedavi edilmiş olan hastalar çalışmaya dahil edilmiştir. Tüm hastalar normal veya azalmış dikey büyüme paternine, normal maksilla ve mandibuler geriliğe sahiptir. Hastalar 2 gruba ayrılmıştır, 15 hasta Twin Block grubu, 14 hasta ise Herbst grubudur. Hastalar Sınıf I molar ve kanin ilişkisine sahip olana kadar fonksiyonel çene ortopedisi tedavisi görmüştür. Kondil ile glenoid fossadaki değişiklikleri 3 boyutlu görüntü ve ölçümlerle saptamak için tedavi öncesi ve sonrasında alınmış olan CBCT görüntüleri üzerinde ölçümler yapılmıştır Çalışma sonucunda, Twin Block ile Herbst grupları arasında tedavi sonuçları açısından, Twin Block grubunun LCoS ve LGfP değerlerinin tedavi başlangicinda Herbst grubuna göre daha az olmasından dolayi tedavi sonunda bu değerlerin Twin Block grubunda daha fazla artması dışında değişiklik gözlenmemiştir. Ayrıca her iki grupta da glenoid fossadaki değişiklikler tüm yönlerde önemsiz bulunmuş olup bireylerin kondillerinin, posterior kısımları hariç, aşağı doğru hareket ettiği tespit edilmiştir. Diğer yandan, her iki grupta da kızlar ve erkekler arasında önemli farklar bulunmamıştır. THREE-DIMENSIONAL ASSESSMENT OF CONDYLE AND GLENOID FOSSA CHANGES AFTER TREATMENT WITH THE TWIN BLOCK AND HERBST APPLIANCES MARIA-FOTEINI VELENTZA SUMMARY The aim of this thesis is to evaluate and compare the 3 dimensional changes occurring in the condyle and glenoid fossa area in patients with Class II skeletal deformities receiving treatment with the Twin Block or Herbst appliances. Twenty nine Class II Division I skeletal patients, who required functional appliance treatment as a part of their orthodontic treatment were selected. All patients were diagnosed with normal or low vertical growth pattern, mandibular deficiency and normal maxilla. The patients were divided into 2 groups,15 being the Twin Block group and 14 the Herbst group. The patients were treated with functional jaw orthopedics till a full Class I molar and canine relationship was achieved. Volumetric measurements were performed preoperatively and postoperatively, in order to reconstruct three dimensional images and measure the changes of the condyle and the glenoid fossa. As a result of our study there were no differences found in the treatment results between the Twin Block and the Herbst group with the exception of the LCoS and LGfP point in the Twin Block group, differences, which were accounted to the smaller pretreatment values in the Twin Block. Moreover in both groups the changes in the glenoid fossa were non-significant in all directions and the condyle of the subjects moved only inferiorly with the exception of its posterior aspect. Meanwhile no important differences were found to exist between males and females in both groups.
Keywords: Ağız ve Diş Sağlığı; Çene; Diş; Ortodonti